Review paper (Folia Neuropathologica, 2012)

(untitled) - Parchi, Piero; Saverioni, Daniela
Human prion diseases are a unique group of transmissible neurodegenerative diseases that occur as sporadic, familial or acquired disorders and show a wide range of phenotypic variation. The latter has been attributed to the existence of distinct strains of the agent or prion, and the genetic background of the host, namely the primary sequence of the gene encoding the prion protein, which is the site of mutations and polymorphisms. The characterization of distinct isoforms of the abnormal prion protein in the brain of affected patients, which has been shown to correlate with the disease phenotype, has recently led to the concept of molecular strain typing, in which the different prion protein isoforms or “types”, possibly enciphering the strain variability in their conformation, may serve as surrogate markers for individual prion strains. In sporadic Creutzfeldt-Jakob disease, the most common human prion disease, there are at least six distinct clinico-pathological disease phenotypes that largely correlate at a molecular level with two prion protein types with distinctive physicochemical properties and the genotype at the methionine/valine polymorphic codon 129 in the prion protein gene. Recent results of transmission studies indicate that five prion strains with distinctive biological properties can be isolated from these six disease variants. It has also been shown that about a third of sporadic cases show a mixed phenotype and the co-occurrence of prion protein types. The origin of prion strains and their co-occurrence as well as the mechanisms underlying the strain-specific neuronal targeting remain largely unexplained and their understanding constitute, together with the development of successful therapies and more sensitive and specific clinical biomarkers, the major challenges that this disease poses for the future.